Characteristic of the active substance of the Saccharomyces cerevisiae preparation having radioprotective properties - G. S. Ritter; V. P. Nikolin; N. A. Popova; A. S. Proskurina; P. E. Kisaretova; O. S. Taranov; T. D. Dubatolova; E. V. Dolgova; E. A. Potter; S. S. Kirikovich; Y. R. Efremov; S. I. Bayborodin; et al. (Вавиловский журнал генетики и селекции)
The paper describes some biological features of the radioprotective effect of double-stranded RNA preparation. It was found that yeast RNA preparation has a prolonged radioprotective effect after irradiation by a lethal dose of 9.4 Gy. 100 % of animals survive on the 70th day of observation when irradiated 1 hour or 4 days after 7 mg RNA preparation injection, 60 % animals survive when irradiated on day 8 or 12. Time parameters of repair of double-stranded breaks induced by gamma rays were estimated. It was found that the injection of the RNA preparation at the time of maximum number of double-stranded breaks, 1 hour after irradiation, reduces the efficacy of radioprotective action compared with the injection 1 hour before irradiation and 4 hours after irradiation. A comparison of the radioprotective effect of the standard radioprotector B-190 and the RNA preparation was made in one experiment. It has been established that the total RNA preparation is more efficacious than B-190. Survival on the 40th day after irradiation was 78 % for the group of mice treated with the RNA preparation and 67 % for those treated with B-190. In the course of analytical studies of the total yeast RNA preparation, it was found that the preparation is a mixture of single-stranded and double-stranded RNA. It was shown that only double-stranded RNA has radioprotective properties. Injection of 160 μg double-stranded RNA protects 100 % of the experimental animals from an absolutely lethal dose of gamma radiation, 9.4 Gy. It was established that the radioprotective effect of double-stranded RNA does not depend on sequence, but depends on its double-stranded form and the presence of “open” ends of the molecule. It is supposed that the radioprotective effect of double-stranded RNA is associated with the participation of RNA molecules in the correct repair of radiation-damaged chromatin in blood stem cells. The hematopoietic pluripotent cells that have survived migrate to the periphery, reach the spleen and actively proliferate. The newly formed cell population restores the hematopoietic and immune systems, which determines the survival of lethally irradiated animals.